Pengaruh Buah Sirsak Terhadap Faktor Risiko Kardiovaskular (Kolesterol Total, HDL, LDL, Trigliserida) - Haidar Alatas (Universitas Muhammadiyah Purwokerto, 2021)
Soursop fruit contains phenolic, tannins, flavonoids. Phenolic inhibit xanthine oxidase inhibitors which inhibit the production of uric acid, this will affect in decreasing cardiovascular risk. Tannins reducing triglyceride levels. Flavonoids reduce HMG-CoA reductase and total cholesterol. Several studies conducted on animal experiments and the results of soursop fruit reduce lipid profile. What is the effect of soursop fruit consumption on cardiovascular risk in healthy humans? This epidemiological research was conducted in Mlati, Sleman, Indonesia. There were 143 subjects that conform to the inclusion and exclusion criteria subsequently randomized to two groups. Group I was given 2x100 g/day of soursop and group II was without soursop. A laboratory examination was conducted of total cholesterol, HDL, LDL, and triglyceride levels at weeks 0, 7, and 13 both in the soursop and non-soursop groups. Regular soursop consumption was evaluated every two weeks for three months. Data analysis was performed using an independent t test, a nonparametric Mann–Whitney test, and a chi-square test. There was no significant difference in total cholesterol (p=0.254 and p=0.932), HDL (p=0.400 and p=0.960), LDL (p=0.221 and p=0.710), triglycerides (p=0.423 and p=0.580) between the soursop and non-soursop groups. The consumption of soursop fruit at 2x100 g/day has no significant effect on improvement in cardiovascular risk (total cholesterol, HDL, LDL, triglycerides) in healthy subjects, but in subjects with hypercholesterolemia and hypertriglyceridemia, the mean cholesterol and triglyceride levels decreased at week 7 and 13 compared to no soursop consumption